2019
DOI: 10.1111/ced.14037
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneotrichosporon ( Trichosporon ) debeurmannianum associated with a subcutaneous mycotic cyst successfully treated with voriconazole

Abstract: Click https://www.wileyhealthlearning.com/ced.aspx for the corresponding questions to this CME article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…Nath et al 14 reported that nine isolates from three blood and six urine samples in patients who were diagnosed as septicemia and urinary tract infection over a 3‐year period. In addition, Noy et al 15 reported the case of a subcutaneous mycotic infection caused by C. debeurmannianum in an immunocompetent man. In our study, the isolated C. debeurmannianum showed high echinocandins MICs.…”
Section: Discussionmentioning
confidence: 99%
“…Nath et al 14 reported that nine isolates from three blood and six urine samples in patients who were diagnosed as septicemia and urinary tract infection over a 3‐year period. In addition, Noy et al 15 reported the case of a subcutaneous mycotic infection caused by C. debeurmannianum in an immunocompetent man. In our study, the isolated C. debeurmannianum showed high echinocandins MICs.…”
Section: Discussionmentioning
confidence: 99%